The Articulation of Transcendence: Aquinas and the Names of God - Franklin, John Mark (My University, 1978)
This thesis deals with St. Thomas Aquinas interpretation of religious language. Particular attention is given to his theory of analogy and its employment in religious language. The first of our four chapters examines Thomas' treatment of univocity and equivocity. Its importance is twofold. First, it introduces the reader to some of the major considerations that lead Aquinas to eventually appeal to analogy in order to explain the meaning of the divine predicates. Secondly, it brings to light certain key metaphysical elements that underpin his analysis of univocity and equivocity, elements which will re-emerge in his application of analogy to religious language. The second chapter examines Thomas' theory of analogy and its employment in the predication of names to God. The third chapter focuses upon a crucial distinction that Aquinas makes between a term's modus significandi (mode of signification) and its res significata (the thing signified). There we provide an account of this distinction and show how it relates to Thomas' interpretation of religious utterances. In the fourth chapter we move towards a critical assessement of Aquinas' handling of religious language, Therein we consider two basic problems that afflict his treatment of the divine predicates. The first involves the agnostic character of Thomas' analysis of these predicates. The second is tied up with the problem of the ratio communis of analogous terms. We conclude the thesis with a number of summary observations on the difficulties that are found in Aquinas' interpretation of religious language.
Keywords: Philosophy; Philosophy